Invariant symmetric restrictions of a self-adjoint operator. II - Dudkin, M. Ye. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We give a criterion of invariance and symmetry of the restriction of an arbitrary unbounded self-adjoint operator in the space L 2(ℝn, dx) by using the introduced notion of support of an arbitrary vector and the notion of capacity of a subspace N ⊂ ℝn.